Leptin stimulates protein synthesis-activating translation machinery in human trophoblastic cells - Pérez Pérez, Antonio (2009)
Leptin was originally considered as an adipocyte-derived signaling molecule for the central control of metabolism. However, pleiotropic effects of leptin have been identified in reproduction and pregnancy, particularly in placenta, where it may work as an autocrine hormone, mediating angiogenesis, growth, and immunomodulation. Leptin receptor (LEPR, also known as Ob-R) shows sequence homology to members of the class I cytokine receptor (gp130) superfamily. In fact, leptin may function as a proinflammatory cytokine. We have previously found that leptin is a trophic and mitogenic factor for trophoblastic cells. In order to further investigate the mechanism by which leptin stimulates cell growth in JEG-3 cells and trophoblastic cells, we studied the phosphorylation state of different proteins of the initiation stage of translation and the total protein synthesis by [3H]leucine incorporation in JEG-3 cells. We have found that leptin dose-dependently stimulates the phosphorylation and activation of the translation initiation factor EIF4E as well as the phosphorylation of the EIF4E binding protein EIF4EBP1 (PHAS-I), which releases EIF4E to form active complexes. Moreover, leptin dose-dependently stimulates protein synthesis, and this effect can be partially prevented by blocking mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3 kinase (PIK3) pathways. In conclusion, leptin stimulates protein synthesis, at least in part activating the translation machinery, via the activation of MAPK and PIK3 pathways. © 2009 by the Society for the Study of Reproduction, Inc.